Economics, Anthropological Models and the Ancient Near East - Warburton, David A. (Anthropology of the Middle East, 2009)
This article discusses the evidence of markets in the Ancient Near East. The major points are (1) the shortcomings of the misguided application of the Polanyi model and (2) the ensuing implications of the failure to integrate economic history into modern economic theory. The analysis concentrates on Ancient Egypt, as it presents the most significant problem for economic history and theoretical modelling. Detailed criticism of the means by which the Polanyi model is upheld is coordinated with an argument in favour of recognising the importance of markets. The argument is that these markets are relevant both to long-term economic history and to modern economic theory – and that this must lead to a new debate about ancient and modern economies.
Keywords: Egypt; Middle East; ancient civilization; anthropology; economic history; economic theory; economics; markets; neo-classical synthesis; technology